Framing Political Success: A Rhetorical Discourse Analysis Of The ‘Gerbang Baru Nusantara’ Jargon In East Java 2024 - Rudi Sutanto; Rino Febrianno Boer (Jurnal Mamangan, 2024)
This study analyzes the political communication strategy of Khofifah Indar Parawansa and Emil Elestianto Dardak in the 2024 East Java Gubernatorial Election. The focus of the study lies in the use of the slogan “Gerbang Baru Nusantara,” which serves not only as a campaign tagline but also as a rhetorical instrument to shape public opinion and media discourse. The analysis shows that ethos was employed to emphasize credibility and bureaucratic experience; pathos to build emotional connections grounded in local identity; and logos through the presentation of concrete programs such as MSME digitalization and regional connectivity development. Within the framework of agenda setting, the slogan successfully redirected public attention to strategic development issues positioning East Java as a significant part of the national development scheme. The slogan was consistently used across various communication channels speeches, social media, public debates, and mass media coverage thus creating collective resonance. The integration of classical rhetoric and agenda-setting strategy illustrates that effective political communication relies not only on linguistic symbolism but also on the ability to manage perception and construct political identity. “Gerbang Baru Nusantara” emerges as a strategic discursive symbol in consolidating electoral support at the regional level